Jual Beli Kapal Laut di Atas Ukuran GT-7 Tanpa Akta Autentik di Kabupaten Morowali Utara - Ince Mochamad Arief Ibrahim; Winner Sitorus; Aulia Rifai (CV. Social Politic Genius (SIGn), 2023)
This research aims to discern and analyze the legal repercussions of selling and purchasing ships over GT-7 size without authentic deeds. This research uses an empirical legal research method. All collected data is then qualitatively analyzed to describe the problem and answer the research objectives. The results show that the preference of the North Morowali community leans more towards the use of receipts as evidence of the sale and purchase of ships over GT-7 size, compared to the formal mechanism of a deed of sale and purchase executed before a Notary. As a result, five ships over GT-7 size operate without Port Clearance, which inevitably places the ship’s captain in a vulnerable position regarding criminal punishment: a maximum imprisonment of five years and a fine of up to IDR 600,000,000. Furthermore, the sale and purchase of ships over GT-7 size without authentic deeds have also resulted in ownership disputes among the local community, as the gross deed of ship registration still lists the previous owner’s identity. Therefore, several recommendations can be proposed to the relevant stakeholders. First, the Harbor Master of Kolonodale Port should conduct intensive socialization regarding the importance of the deed of sale for ships over GT-7 size executed before a Notary. This socialization aims to ensure the clear legal status of ships, raise public awareness about safety and seaworthiness, and prevent potential criminal punishment risks for the captain. Second, as Government Officials, the Ship Registration Officer and Ship Name Transfer Recorder should collaborate with legal institutions to review ships operating in Indonesian waters without Port Clearance. Lastly, Law Enforcement should adopt a mediation approach in resolving ship ownership disputes, prioritizing aspects of justice and truth, thereby preventing further losses for the Northern Morowali community.